Early detection of psoriatic arthritis in patients with psoriasis: construction of a multifactorial prediction model - Wang, Chunxiao; Wang, Sihan; Liu, Liu; Wang, Jiao; Cai, Xiaoce; Zhang, Miao; Sun, Xiaoying; Li, Xin (Frontiers in Immunology, 2024)
Psoriatic arthritis (PsA) affects approximately one in five individuals with psoriasis. Early identification of patients with psoriasis at risk of developing PsA is crucial to prevent poor prognosis. We established a derivation cohort comprising 1,661 patients with psoriasis from 49 hospitals. Clinical and demographic variables ascertained at hospital admission were screened using the Least Absolute Shrinkage and Selection Operator and logistic regression to construct a prediction model and a new web-based calculator. Ultimately, six significant independent predictors were identified: history of unexplained swollen joints (odds ratio [OR]: 5.814, 95% confidence interval [95% CI]: 3.304–10.117; p< 0.001), history of arthritis (OR: 3.543, 95% CI: 1.982–6.246; p< 0.001), history of unexplained swollen and painful fingers or toes (OR: 2.707, 95% CI: 1.463–4.915; p = 0.001), nail involvement (OR: 1.907, 95% CI: 1.235–2.912; p = 0.003), hyperlipidemia (OR: 4.265, 95% CI: 0.921–15.493; p = 0.042), and prolonged topical use of glucocorticosteroids (OR: 1.581, 95% CI: 1.052–2.384, p = 0.028). The web-based calculator derived from this model can assist clinicians in promptly determining the probability of developing PsA in patients with psoriasis, thereby facilitating improved clinical decision-making.